Comparative study of the reliability of some deterministic and stochastic interpolation methods for ground bearing capacity mapping: Case of the Olembé social housing site in Cameroon (International Journal of Geoscience, Engineering and Technology, 2022)
This paper deals with the comparative study of the reliability of some deterministic and stochastic interpolation methods for ground bearing mapping. Covering an area of 121,481.65 m², the site covered by this study is located in the locality of Olembé in the central region of Cameroon. The methodology consisted of collecting from the Ministry of Housing and Urban Development the results of the tests relating to the bearing capacity of the soil for depths of 1.2m, 2.4m and 4.5m as well as the location of the sounding points. Using ARCGIS mapping software, ground bearing mapping was performed by Inverse Distance Weighting (IDW) and Local Polynomial Interpolation (LPI) as deterministic interpolation methods while Ordinary Kriging (KO) and Empirical Bayesian Kriging (KBE) were retained as stochastic methods. The comparative analysis of the interpolation error according to the different methods studied shows that the stochastic methods are the most precise and the empirical Bayesian kriging is the most precise of all. The interpolation error between 8.1% and 41.20% for the deterministic methods while for the stochastic methods it is between 0.4% and 8.80%. The minimum average of bearing capacity recorded for the deterministic methods is 2.35 bars, 3.52 bars, 1.89 Against 1.58bars, 2.42bars and 1.75 bars for the stochastic methods at a depth of 1.2m, 2.4m and 4.5m respectively.